Cr-metal-organic framework coordination with ZnIn2S4 nanosheets for photocatalytic reduction of Cr(VI). (20th March 2022) - Zhang, Lu; Qiu, Jianhao; Dai, Dingliang; Zhou, Yichen; Liu, Xi; Yao, Jianfeng
Abstract: MIL-101(Cr)@ZnIn2 S4 hierarchical heterojunction was delicately designed and fabricated through the in-situ growth of ZnIn2 S4 on MIL-101 and electrostatic self-assembly. It is affirmed that the Cr–S interface bonding between MIL-101 and ZnIn2 S4 in their composite was established based on the characterization results of X-ray photoelectron spectroscopy, Raman and zeta potential. Thus, a high-speed channel for charges transfer is offered due to the Cr–S bond, intimate interface contact and hierarchical structure of MIL-101@ZnIn2 S4, which largely inhibits the recombination of photo-induced charge carriers and promises a remarkable photocatalytic activity. Choosing visible-light-driven reduction of Cr(VI) as a model, the optimal MIL-101@ZnIn2 S4 sample can reduce 95% of Cr(VI) within 30 min, corresponding to a rate constant of 0.107 min −1, which is 2.9-fold compared with blank ZnIn2 S4 counterpart (MIL-101 has a negligible performance). Additionally, a conspicuous apparent quantum yield of 9.7% can be achieved at a wavelength of 420 nm. Eventually, to reinforce the practicability of MIL-101@ZnIn2 S4, the composite powders were manufactured as aerogels utilizing bacterial cellulose as a substrate. The MIL-101@ZnIn2 S4 aerogel still exerts an enviable performance for photocatalytic reduction of Cr(VI) and stability. This work could inspire the material design and environmental remediation based on MOFs. Graphical abstract: Image 1 Highlights: MIL-101@ZnIn2 S4 hierarchical heterojunction with Cr–S bonds was delicately designed. A high-speed channel for charges transfer is presented over MIL-101@ZnIn2 S4 . Efficiently photocatalytic reduction of Cr(VI) is achieved over MIL-101@ZnIn2 S4 . Aerogel was prepared from powder to improve the practicability of MIL-101@ZnIn2 S4 .